A relação entre os saberes e o acesso à justiça e a direitos: a visão normativista e técnico-formal do Direito é suficiente para solucionar violações de direitos vivenciadas pela população vulnerável? - Taveira, Rachel de Miranda (2022)
The themes of the present work are the articulation between knowledge and collective access to justice and rights and the objective of this master's dissertation is to answer the following question: The normativist and technical-formal vision of law is sufficient to solve violations of rights experienced by the vulnerable population? For that, it worked with three hypotheses. The first hypothesis is that the normative and technical-formal view of law is insufficient to solve violations of collective rights of the vulnerable population, since it does not consider society's desires for justice and for the effectiveness of rights. The second hypothesis, that violations of the collective rights of vulnerable people are characterized as complex demands, as they present specificities different from those achieved by the norm, its methods and techniques. Therefore, they require innovative responses to solve traditional demands. The third, that the relationship between knowledge and collective access to justice and rights allows the elaboration and use of effective instruments to seek to solve such complex demands, exemplifying the case of the Public Defender's Office. As for the methodology, the hypothetical-deductive method of qualitative design was used. Data collection, for the characterization of the theories developed, took place from the reading and bibliographic analysis, articles, theses and monographs that deal with the themes, available in physical and virtual media (secondary sources). For the case analyzed, the Public Defender institution, the data were taken from both secondary sources and from the Revistas da Defensoria Pública do Estado de São Paulo, available virtually on the institution's website. All data were analyzed based on the exposed concepts. Finally, the research related the themes and other concepts worked with the analyzed case, using deductive logical reasoning and verified that the normative and technical-formal theory of law is not enough to solve the complex demands of the vulnerable population and that interdisciplinarity and collective access to justice and collective rights present ways to guarantee justice and the effectiveness of rights